Design of Liquified Petroleum Gas (LPG) Leak Detection Tool with Buzazer nd Telegram based on IOT - Maisarah, Siti Maisarah; Samsudin, Samsudin; Jibril, Muhammad; Prasetyo, Dwi Yuli; Zulrahmadi, Zulrahmadi (Sistemasi: Jurnal Sistem Informasi, 2024)
The development of Internet of Things (IoT) technology has made a major contribution to increasing efficiency and security in various fields. One of the growing applications is the use of IoT in gas leak detection to maintain a safe environment. This research aims to design an IoT-based gas leak detection tool using the MQ-2 sensor with a case study at a village office. The tool designed integrates the MQ-2 sensor to detect dangerous gases such as Liquified Petroleum Gas(LPJ), propane and methane, and uses a buzzer as a sound warning and Telegram as a communication platform to provide real-time notifications. A case study was conducted at the village office to test the effectiveness of the tool in detecting gas leaks and providing a fast response. The research results show that the gas leak detection tool developed is able to accurately detect dangerous gases and provide early warning via buzzer and Telegram. The integration of IoT in this tool provides an efficient solution in maintaining environmental security, especially in village office environments. This research is expected to contribute to the development of IoT-based gas leak detection technology and provide guidance for the use of similar tools in various environments. In addition, case studies in village offices provide examples of relevant implementation in the context of environmental safety in the workplace.